Kritik Pemikiran Relativisme Moral yang Dibangun dari Temuan di Bidang Neuroscience - Maolani, Mimi (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2023)
CRITICISM OF MORAL RELATIVISM THOUGHT CONSTRUCTED FROM FINDINGS IN THE FIELD OF NEUROSCIENCE. This paper aims to criticize the idea of moral relativism which is built from new findings in neuroscience. This idea is often propagated while placing the morality of religious people as irrational, far-fetched and out of date. This is a challenge for the propagation of rational and universal Islamic moral values. Da’i need to understand the antithesis of this thought in order to be able to answer their arguments in the field of da'wah. This study uses a qualitative method and critical analysis approach. Critical analysis based on theory of coherence, correspondence and pragmatics. The weakness of this thought is reduce morality to be just sympathy, and negate other aspects of moral formation. The approaches and methods used are not right. The conclusion of moral relativism from arguments and scenarios of moral judgment in a neuroscience experiment is illegitimate, instead this studi discovered the rationality, objectivity and universality of the moral value behind the proposed argument. This relativism idea cannot be applied in non-social moral judgments, causing people to be skeptical of rational explanations of moral judgement, and make moral decisions instinctively without measure the impact of their actions on their goals, thus bringing badness to themselves and their environment.